Respuesta :
Hi there!
To solve this using substitution, we substitute the value of y in the equation.
5x + 8 = 8x + 9
Now, we simplify.
8 = 3x + 9
-1 = 3x
x = -1/3
We plug the value of x in,
y = 5 (-1/3) + 8
y = -1 2/3 + 8
y = 6 1/3
Hope this helps!
To solve this using substitution, we substitute the value of y in the equation.
5x + 8 = 8x + 9
Now, we simplify.
8 = 3x + 9
-1 = 3x
x = -1/3
We plug the value of x in,
y = 5 (-1/3) + 8
y = -1 2/3 + 8
y = 6 1/3
Hope this helps!
y = 5x + 8 --------(1)
y = 8x + 9
=> 8x - y + 9 = 0 --------(2)
On Substituting equation (1) in (2), we get
8x - 5x - 8 + 9 = 0
=> 3x +1 = 0
=> x = - 1 /3
Now,
On Substituting the value of x in equation (1), we get
y = 5 (-1/3) + 8
y = - 5/3 + 8
y = (-5 + 24) /3
y = 19/3
y = 8x + 9
=> 8x - y + 9 = 0 --------(2)
On Substituting equation (1) in (2), we get
8x - 5x - 8 + 9 = 0
=> 3x +1 = 0
=> x = - 1 /3
Now,
On Substituting the value of x in equation (1), we get
y = 5 (-1/3) + 8
y = - 5/3 + 8
y = (-5 + 24) /3
y = 19/3